A manifestação do sublime em Manoel de Barros - Soares, Ana Paula de Toledo (2015)
The dissertation presents an approach of sublime aesthetics in nature, with reading of the Manoel de Barros poems presents in the books O Guardador de Águas (1989) e Menino do mato (2010). The study performs reflection about the sublime feeling, as well as expands the area of knowledge about the poetics of the author. The research proposes a theoretical approach of the sublime in a historical and conceptual aspects, for a better understanding of its transformation over time, as well as the aesthetization of the nature and poetic image created in the texts to provide basis for thinking the sublime in the poetry. The corpus selected shows that the aesthetics of the sublime is still present in the texts and its basis are the same faculty of imagination and faculty of reason what changes is the form of scenarios composition, transforming the way of feeling. Reading Manoel de Barros, the feeling is awakened with the stimulus of the faculty of imagination, generating estrangement followed by delight, which produces the negative pleasure of the sublime